Fear of COVID-19 and its associations with perceived personal and family benefits and harms in Hong Kong. Issue 3 (23rd March 2021) - Sit, Shirley Man-Man; Lam, Tai-Hing; Lai, Agnes Yuen-Kwan; Wong, Bonny Yee-Man; Wang, Man-Ping; Ho, Sai-Yin
Abstract: Fear of COVID-19 is associated with public health compliance but also with negative well-being; however, no articles have reported associations of such fear with perceived benefits and harms. We assessed the level of fear of COVID-19 in Hong Kong adults and its associations with sociodemographic factors and perceived benefits and harms of COVID-19. In a 6-day population-based cross-sectional online survey in May 2020, 4, 890 adults provided data on fear and perceived benefits and harms, personal happiness and family well-being, and sociodemographic characteristics. Linear regression was used to analyze associations. The level of fear was moderate (mean score 6.3/10). Fewer respondents reported perceived benefits (10.6%–21.7%) than harms (13.4%–43.5%). Females, younger age groups, and respondents with lower education or more cohabitants had greater fear. Fear was associated with perceived personal (increased knowledge of personal epidemic prevention) and family benefits (improved family hygiene), both with a very small effect size (Cohen's d = 0.03). Fear was also associated with lower personal happiness and perceived personal (increased negative emotions, feeling depressed and anxious, decreased income, and decreased work efficiency) and family harms (increased conflicts and negative emotions among family members), with small effect sizes (0.08–0.37). We have first shown sociodemographic differences in the fear of COVID-19 and such fear was associated with both perceived personal and family benefits and harms of COVID-19. Our findings may guide the management of fear to reduce sociodemographic differences, and maximize benefits and minimize harms. Abstract : Females, younger people, those with lower education or more cohabitants had greater fear of COVID-19. Such fear was associated with both perceived personal and family benefits and harms.